The effect of climbing ability and slope inclination on vertical foot loading using a novel force sensor instrumentation system - Baláš, Jiří; Panáčková, Michaela; Jandová, Soňa; Martin, Andrew J; Strejcová, Barbora; Vomáčko, Ladislav; Charousek, Jan; Cochrane, Darryl J; Hamlin, Mike; Draper, Nick (Journal of human kinetics, 2014)
The aim of the study was to assess the effects of climbing ability and slope inclination on vertical loading both in terms the forces involved and physiological responses. Five novice and six intermediate female climbers completed a climbing route at three slope inclinations (85°, 90°, and 98°). The vertical loading during the climb was assessed by force-time integral using a Novel Pedar-X insole and physiological responses via oxygen uptake and heart rate. The novice climbers had a significantly lower (p < 0.05) vertical loading on foot holds and higher oxygen uptake and heart rate compared to intermediate climbers. A significant negative correlation was identified between the force-time integral and oxygen uptake (R = -0.72), and with heart rate (R = -0.64), respectively. The time-force integral decreased across the ascents with increasing slope inclination (p < 0.001). The results indicate that more advanced ability climbers make greater use of foot holds, with associated lowering in physiological response (oxygen uptake and heart rate) across all slope inclinations.
Keywords: oxygen uptake; vertical force; Pedar X insole; indoor climbing; force sensor